Averrhoa carambola leaves prevent dyslipidemia and oxidative stress in a rat model of poloxamer-407-induced acute hyperlipidemia - Abduh, Maisa Siddiq; Saghir, Sultan A. M.; Al Hroob, Amir M.; Bin-Ammar, Albandari; Al-Tarawni, Ayat H.; Murugaiyah, Vikneswaran; Mahmoud, Ayman M. (Frontiers in Pharmacology, 2023)
Background: The star fruit (Averrhoa carambola L. (Oxalidaceae)) is traditionally used in the treatment of many ailments in many countries. It possesses several pharmacological activities, including antioxidant and anti-inflammatory effects. However, it contains the neurotoxic caramboxin and its high content of oxalic acid that limits its consumption by individuals with compromised kidney function. This study assessed the anti-hyperlipidemic and antioxidant activities of different fractions of the methanolic extract of A. carambola leaves (MEACL). Methods: The antioxidant activity was investigated using FRAP, ABTS and DPPH radical-scavenging assays and the inhibitory activity toward pancreatic lipase (PL) and HMG-CoA reductase was assayed in vitro. Acute hyperlipidemia was induced by poloxamer-407 (P-407) in rats and different fractions of MEACL (n-hexane, chloroform, n-butanol, ethyl acetate (EA), water, and chloroform) were orally administered. Cholesterol and triglycerides were determined at 0, 12, 24 and 48 h and LDL-C, vLDL-C, HDL-C, lipid peroxidation (LPO) and antioxidants were assayed after 48 h. The expression of ABCA1, ABCG5, ABCG8, LDL-R, SREBP-1 and SREBP-2 and the activity of HMG-CoA reductase were assayed in the liver of P-407-administered rats treated with the EA fraction. Results: The in vitro data revealed potent radical-scavenging activities of MEACL fractions with the most potent effect showed by the EA fraction that also suppressed the activities of HMG-CoA reductase and PL. In P-407-induced hyperlipidemic rats, all fractions prevented dyslipidemia as shown by the decrease in total cholesterol, triglycerides, LDL-C, vLDL-C and atherogenic index. MEACL and its fractions prevented LPO and boosted GSH, superoxide dismutase, glutathione peroxidase, and catalase in P-407-administered rats. The EA fraction showed more effective anti-hyperlipidemic and antioxidant effects than other fractions and downregulated SREBP-2 while upregulated ABCA1 and LDL-R and ameliorated LPL and HMG-CoA reductase in hyperlipidemic rats. Conclusion: MEACL showed in vitro and in vivo antioxidant activity and the EA fraction significantly ameliorated dyslipidemia in a rat model of P-407-induced acute hyperlipidemia by modulating LPL, PL, HMG-CoA reductase, and cholesterolgenesis-related factors. Therefore, the leaves of A. carambola represent a safe alternative for the star fruit particularly in kidney disease patients, and the EA is the most effective anti-hyperlipidemic and antioxidant fraction.